2018
DOI: 10.1002/slct.201803030
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Assisted Emission Enhancement of 2‐Hydroxynaphthaldoxime and Related Compounds

Abstract: The combined contributions from the excited‐state intramolecular proton‐transfer and aggregation‐induced emission in the photoluminescence of compounds namely 2‐hydroxynaphthaldoxime, 2‐methoxynaphthaldoxime, 2‐hydroxynaphthaldehyde and 1‐[(methylimino)methyl]naphthalen‐2‐ol were established. For such a purpose the changes in the fluorescence emission of these compounds in different solvents upon addition of water and from the fluorescence emission life‐time decay profiles were studied. 1H‐NMR titration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The packing pattern revealed that a grid-like structure having rectangular barricades was formed by the self-assembled anions, where the tetrabutylammonium cations were trapped (Figure c). This observation complemented our earlier findings on the encapsulation of tetrabutylammonium cations in the rectangular voids of the gridlike structure of the hydrogen-bonded anions of oxime molecules. , (TBA) + (H2Sulfaurea) – had a different in thermal stability in comparison to the DMF solvates. A themogravimetric study showed that the salt decomposed on heating above 200 °C (Figure S31).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The packing pattern revealed that a grid-like structure having rectangular barricades was formed by the self-assembled anions, where the tetrabutylammonium cations were trapped (Figure c). This observation complemented our earlier findings on the encapsulation of tetrabutylammonium cations in the rectangular voids of the gridlike structure of the hydrogen-bonded anions of oxime molecules. , (TBA) + (H2Sulfaurea) – had a different in thermal stability in comparison to the DMF solvates. A themogravimetric study showed that the salt decomposed on heating above 200 °C (Figure S31).…”
Section: Resultssupporting
confidence: 89%
“…The hydrogen bond angles involving the halide ion as the central ion in the individual cocrystal had a distorted Y shape. Depending on the hydrogen bond donors and shapes of the receptors, a halide ion may adopt different anion coordination geometries, among which a T shape has been commonly observed.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, Oxm-108 , which is mildly emissive in DMSO, becomes extremely blue-emissive in a 90% water–DMSO solvent mixture. 163 Oxime derivative Oxm-110 forms various transition metal complexes with Cu( ii ), Ni( ii ), and Zn( ii ) ions. These complexes have been utilized for the selective and sensitive detection of fluoride ions, even in the presence of other competitive anions.…”
Section: Oxime Derivatives In Recognitions Of Anionsmentioning
confidence: 99%
“…Naphthaldehyde-based compounds have numerous presentations such as electrochemical, catalytic, photoluminescence, analytical, cytotoxic, antimicrobial and in vitro anticancer, antiproliferative, antioxidant, catechol's studies [33][34][35][36][37][38][39][40][41][42][43] Transition metal compounds play important role in bio-inorganic chemistry and redox enzyme systems [44]. Copper is one of the most important elements in the human body.…”
Section: Introductionmentioning
confidence: 99%